The History and Development of Madrasa in Indonesia - Fajar Syarif (IAIN Bengkulu, 2020)
This study is aimed to find out how the journey of madrasah’s history from classical to modern times, from middle east to Indonesia, as well as the challenges for the sake of existence. To achieve these objectives, the author uses library research, using written materials that have been published as books and international journals. This study uses a historical approach and science education. The results of this study indicate that growth and development of madrasah’s history in Indonesia there are two momentum determines the existence of Madrasah. First, SKB 3 minister in 1975 that became the entrance of madrasah recognition as an islamic educational institution equivalent to public shcools. Second, National Education System Law no. 2/1989 makes madrasah not only as an educational institution equivalent to public schools, more than that, madrasah is an islamic educational institution or public institution that has islamic characteristic. And well known as a PLUS public school. but on the other hand is also a challange that needs to be evidence, whether madrasah able to assume the dual status.